Appropriate Systemic Therapy Dosing for Obese Adult Patients With Cancer: ASCO Guideline Update. Issue 18 (20th June 2021) - Griggs, Jennifer J.; Bohlke, Kari; Balaban, Edward P.; Dignam, James J.; Hall, Evan T.; Harvey, R. Donald; Hecht, Diane P.; Klute, Kelsey A.; Morrison, Vicki A.; Pini, T. May; Rosner, Gary L.; Runowicz, Carolyn D.; et al.
Abstract : PURPOSE: To provide recommendations for appropriate dosing of systemic antineoplastic agents in obese adults with cancer. METHODS: A systematic review of the literature collected evidence regarding dosing of chemotherapy, immunotherapy, and targeted therapies in obese adults with cancer. PubMed and the Cochrane Library were searched for randomized controlled trials, meta-analyses, or cohort studies published from November 1, 2010, through March 27, 2020. ASCO convened an Expert Panel to review the evidence and formulate recommendations. RESULTS: Sixty studies, primarily retrospective, were included in the review. Overall, the evidence supported previous findings that obese adult patients tolerate full, body-size–based dosing of chemotherapy as well as nonobese patients. Fewer studies have addressed the dosing of targeted therapies and immunotherapies in relation to safety and efficacy in obese patients. RECOMMENDATIONS: The Panel continues to recommend that full, weight-based cytotoxic chemotherapy doses be used to treat obese adults with cancer. New to this version of the guideline, the Panel also recommends that full, approved doses of immunotherapy and targeted therapies be offered to obese adults with cancer. In the event of toxicity, the consensus of the Panel is that dose modifications of systemic antineoplastic therapies should be handled similarly for obese and nonobese patients. Important areas for future research include the impact of sarcopenia and other measures of body composition on optimal antineoplastic dosing, and more customized dosing based on pharmacokinetic or pharmacogenetic factors. Additional information is available at www.asco.org/supportive-care-guidelines .